Predictors of Hooking Up Sexual Behaviors and Emotional Reactions Among U.S. College Students - Lewis, Melissa A. (Arch Sex Behav, 2011)
The present study examined factors associated with engaging in oral and vaginal sex and condom use during the most recent hookup, a term that refers to a range of physically intimate behaviors outside of a committed relationship, among college students. In addition, this research aimed to evaluate factors associated with experiencing positive and negative affect resulting from the most recent hookup. A random sample (N = 1,468) of undergraduates (56.4% female) completed a Web-based survey that was comprised of measures of drinking and sexual behavior. Participants (n = 824; 56.1%) who indicated they had ever hooked up were included in data analysis. Findings indicated that sex, partner type, alcohol use, attitudes towards hooking up, and attitudes towards sexual activity during hookups explained significant variance for oral sex, vaginal sex, condom use, and positive and negative affect related to the most recent hookup experience. Clinical implications regarding the role of situational stressors, such as the impact on affect following a hookup, and ways to reduce risks associated with stressors are discussed.